Resolva essa equação:
2.(x -2)+5.(2-x)+6.(x+1)= 0
Soluções para a tarefa
Respondido por
7
2x - 4 + 10 - 5x + 6x +6 = 0
3x + 12 = 0
x = -4
3x + 12 = 0
x = -4
Respondido por
7
2 (x - 2) + 5 (2 - x) + 6 (x + 1) = 0
2x - 4 + 10 - 5x + 6x + 6 = 0
2x - 5x + 6x = 4 -10 - 6
3x = -12
x = -12 / 3
x = -4
2x - 4 + 10 - 5x + 6x + 6 = 0
2x - 5x + 6x = 4 -10 - 6
3x = -12
x = -12 / 3
x = -4
Perguntas interessantes
Inglês,
10 meses atrás
Matemática,
10 meses atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Filosofia,
1 ano atrás
Geografia,
1 ano atrás